The Relationship Between Abdominal Body Composition and Metabolic Syndrome After a Weight Reduction Program in Adult Men with Obesity - Liao CC (Dove Medical Press, 2020)
Chun-Cheng Liao,1,2 Wayne Huey-Herng Sheu,3–5 Shih-Yi Lin,4,6 Wen-Jane Lee,7 I-Te Lee3,4,8,9 1Department of Family Medicine, Taichung Armed Forces General Hospital, Taichung, Taiwan; 2School of Medicine, National Defense Medical Center, Taipei, Taiwan; 3Division of Endocrinology and Metabolism, Department of Internal Medicine, Taichung Veterans General Hospital, Taichung, Taiwan; 4School of Medicine, National Yang-Ming University, Taipei, Taiwan; 5Rong Hsing Research Center for Translational Medicine, College of Life Sciences, National Chung Hsing University, Taichung, Taiwan; 6Center for Geriatrics and Gerontology, Taichung Veterans General Hospital, Taichung, Taiwan; 7Department of Medical Research, Taichung Veterans General Hospital, Taichung, Taiwan; 8School of Medicine, Chung Shan Medical University, Taichung, Taiwan; 9College of Science, Tunghai University, Taichung City, TaiwanCorrespondence: I-Te LeeDivision of Endocrinology and Metabolism, Department of Internal Medicine, Taichung Veterans General Hospital, 1650 Taiwan Boulevard, Sect. 4, Taichung 40705, TaiwanTel +886-4-23741300Fax +886-4-23593662Email itlee@vghtc.gov.twPurpose: To assess the relationship between changes in abdominal adipose tissue and metabolic syndrome (MetS) in men with obesity after a weight reduction program (WRP).Patients and Methods: Adult men with obesity and MetS were recruited for this prospective single-arm intervention study. Participants consumed an energy-restricted diet of 1200 kcal/day and performed 50-mins aerobic exercise daily for 12 weeks. Changes in the components of MetS were recorded. Changes in subcutaneous abdominal fat area (SAFA) and intra-abdominal fat area (IAFA) at the umbilicus level were determined using magnetic resonance imaging.Results: A total of 30 men (mean age, 42.3 ± 10.0 years; body mass index, 33.7 ± 4.1 kg/m2) were included in this study. A moderate (8.0%) weight reduction occurred. Reversion of MetS was observed in 15 (50%) participants after the WRP. There was significant reduction in SAFA (68.3 ± 20.2 vs. 51.5 ± 18.6 cm2; P < 0.001) and IAFA (96.3 ± 15.6 vs. 86.0 ± 16.5 cm2; P < 0.001); the magnitude of reduction was greater for SAFA than for IAFA (−16.8 ± 7.7 vs. −10.3 ± 8.3 cm2; P < 0.001). Multivariate logistic regression analysis showed a reduction in IAFA to be an independent factor to decrease the risk of persistent MetS after WRP by adjustment for age, baseline IAFA, and change in SAFA (odds ratio = 0.25, 95% confidence interval: 0.07–0.95, P = 0.041). Reduction in SAFA was not significantly associated with the reversion of MetS (P = 0.411).Conclusion: Reduction in IAFA via a 12-week WRP may help reverse MetS in men with obesity and MetS.Keywords: body mass index, intra-abdominal fat, magnetic resonance imaging, metabolic syndrome, subcutaneous abdominal fat, visceral fat